The Agricultural Development of the West During the Civil War - Fite, Emerson D. (Quarterly Journal of Economics, 1906)
Journal Article The Agricultural Development of the West during the Civil War Get access Emerson D. Fite Emerson D. Fite Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 2, February 1906, Pages 259–278, https://doi.org/10.2307/1883656 Published: 01 February 1906